Along‐Slope Variability of Cross‐Slope Eddy Transport in East Antarctica - Annie Foppert; Stephen R. Rintoul; Matthew H. England (Geophysical Research Letters)
Abstract Circumpolar Deep Water (CDW) transport across the Antarctic continental slope regulates the delivery of heat to the shelf and its availability to melt floating ice shelves. The cross‐slope density field, calculated from profiles collected by conductivity‐temperature‐depth‐tagged marine mammals on the East Antarctic slope (0–160°E, above 1,000‐ to 3,000‐m isobaths), indicates eddy‐driven overturning: onshore transport of CDW and offshore transport of shallower Antarctic Surface Water. Enhanced eddy activity, determined by a spice standard deviation threshold in the CDW layer, is present over about a third of the East Antarctic slope analyzed. Significantly stronger CDW transport in regions of elevated spice variability produces subsurface temperature anomalies of 0.2–0.25 °C relative to the East Antarctic average. Estimating eddy diffusivity from the hydrography yields about 0.8 m2/s of warm CDW transport to the shelf break in high‐variability regions. Variability of eddy‐induced CDW transport influences the reservoir of heat available for transport across the shelf break.